Innovations in higher medical education: literature review - Kulichenko, Alla; Куліченко, Алла Костянтинівна (Одеса : Причорномор. н.-д. ін-т екон. та інновацій, 2020)
The article considers the definitions of “innovation” and “innovation activity”, which are presented in domestic and foreign scientific spaces. Systematization of definitions in two directions is carried out: 1) reference and abstract publications; 2) legislative acts and normative documents. The author establishes that due to interpretations of the term “innovation”, which differ depending on the areas of activity, in the modern domestic educational discourse there is no unambiguous definition. In domestic reference sources, the concept of “innovation” is broader than in foreign ones, but, in general, refers to new methods, tools, and products. Besides, the article points out that the definition of “innovation” is virtually absent in most domestic reference books in contrast to foreign literature, where this term is most often used. Moreover, the author notes that the concept of “innovation activity” exists in the Ukrainian legal framework, in particular in the Law of Ukraine “On investment activity” (1991) and the Law of Ukraine “On innovation activity” (2002). The study also states that international legal acts and regulatory documents contain a single definition of innovation, which, despite its name in the original version – research and development (R&D) – fully corresponds to the essence of the term “innovation activity” in the Ukrainian scientific space. As for higher medical education in the US, the definition of innovation is identical to the one formulated in the Frascati Manual (2015). Beyond this document, innovation activity is a systematic creative effort to increase the stock of knowledge, including the knowledge of humanity, culture, and society, and to identify new areas of application of existing knowledge. Among other things, innovation activity must meet five main criteria: novelty; creativity; uncertainty; consistency; ability to transmit and/or reproduce. Concerning the prospects of further research, we are going to analyze scientific and educational works of domestic and foreign scientists regarding the interpretation of the terms “innovation” and “innovation activity”, their use in medical education. У статті розглянуто дефініції понять «інновація» та «інноваційна діяльність», представлені у вітчизняному та зарубіжному наукових просторах. Здійснено систематизацію визначень за двома напрямами: 1) довідкові та реферативні видання; 2) законодавчі акти та нормативні документи. Встановлено, що з огляду на трактування терміна «інновація», які відрізняються залежно від сфер діяльності, у сучасному вітчизняному освітньому дискурсі відсутня його однозначна дефініція. У вітчизняних довідкових джерелах поняття «інновація» є ширшим, ніж у зарубіжних, проте загалом позначає нововведення, нові методи, засоби та продукти діяльності. З’ясовано, що визначення поняття «інноваційна діяльність» практично відсутні у більшості вітчизняних довідкових видань на противагу зарубіжній літературі, де найчастіше цей термін використовують. Поняття «інноваційна діяльність» є в українській нормативно-правовій базі, зокрема у Законі України «Про інвестиційну діяльність» (1991) та Законі України «Про інноваційну діяльність» (2002). Констатовано, що у міжнародних законодавчих актах і нормативних документах фігурує єдине визначення інноваційної діяльності, що, попри свою назву в оригінальному варіанті – наукові дослідження та розвиток (research and development), цілком відповідає сутності терміна «інноваційна діяльність» в українському науковому просторі. Що стосується вищої медичної освіти США, то визначення інноваційної діяльності ідентичне сформульованому в «Керівництві Фраскаті» (2015). За цим документом, інноваційна діяльність є систематичною творчою роботою з метою збільшення запасу знань, серед яких знання людства, культури й суспільства, і визначення нових галузей застосування наявних знань. Інноваційна діяльність має задовольняти п’ять основних критеріїв: новизну; креативність; невизначеність; систематичність; здатність до передачі та / або відтворення. Перспективами подальших розвідок є огляд наукових і навчально-методичних праць вітчизняних і зарубіжних учених щодо тлумачення термінів «інновація» та «інноваційна діяльність», їх використання у медичній освіті.
Інновації у вищій медичній освіті: огляд літератури
Keywords: domestic educational space; foreign educational space; innovation; innovation activity; higher medical education; вітчизняний освітній простір; зарубіжній освітній простір; інновація; інноваційна діяльність; вища медична освіта